Netconf Element Management System : Design and Implementation - Bertolina, Martín (2012)
The Network Configuration Protocol (Netconf) is an IETF network management protocol using an RPCbased communication model. It was developed in the Netconf working group and published in December 2006 as RFC 4741 and later revised in June 2011 (RFC 6241). This protocol defines a simple mechanism through which a network device can be managed, configuration data information can be retrieved, and new configuration data can be uploaded and manipulated. The protocol allows the device to expose a full and formal application programming interface (API). Applications can use this straightforward API to send and receive full and partial configuration data sets.